Occurrence of Verticillium chlamydosporium Goddard in a black pepper (Piper nigrum L.) garden in Kerala, India - RAMANA, T P SREEJA, SANTHOSH J EAPEN, K V (Journal of Spices and Aromatic Crops, 1996)
Verticillium chlamydosporium was isolated and identified for the first time from cases of a semi-endoparasitic nematode, Trophotylenchulus piperis, from an infested black pepper (Piper nigrum) garden in Calicut District of Kerala, India. The fungus suppressed hatching of root knot nematode (Meloidogyne incognita) eggs by 41.4 per cent within 5 days in an in vitro bioassay and appears promising for the control of root knot nematodes of spice crops.